Financial Conditions and the Time Path of Equipment Expenditures - Gardner, Roy; Sheldon, Russell (The Review of Economics and Statistics, 1975)
T HE standard neoclassical investment analysis postulates a fixed timing relationship between changes in the determinants of the desired stock of capacity and actual investment responses these changes elicit.' There are, however, good reasons to suppose that no such fixed timing relationship exists. This paper seeks to explore one class of variables which could influence firms' decisions concerning the time shape of the investment response to a given change in the desired stock of capacity. The influence of financial conditions on firms' investment decisions has long been recognized.2 What we hope to show is that firms will react differently to a given change in the desired stock of capacity if they are faced with differing financial constraints. Financial variables will play a dual role in the analysis. First, as will be evident below, standard neoclassical investment analysis requires a discount rate to determine the optimal equipment-output ratio. We believe that this discount rate is only mildly responsive to changes in financial market conditions. The relevant discount rate, which includes a substantial risk premium, should exhibit less variance over time than the short term cost of funds.3 Reasons for this lie in the ex post fixity of factor proportions and long term nature of investment in equipment. Financial variables should, however, exert an important impact on the time path chosen for the investment response to a given change in desired capacity. We assume that the cost of funds to the firm depends on the firm's ability to utilize retained earnings (cash flow) as well as the coniditions prevailing in the bond and equity markets. Cost is interpreted in a broad sense and definitely includes the risks which management may believe non-internal financing entails.4 Given this view of firm behavior, we expect that the firm will invest more slowly or postpone investment if it expects that either (a) the costs of not having needed capacity in place are outweighed by the gains to be had from making more extensive use of internal sources of finance during a slow expansion, or (b) the costs of outside sources of finance (or the opportunity cost connected with the investment use of retained earnings) will be lower during subsequent periods to such an extent that it is worth the delay. Firms may hasten their investment response even if this involves additional costs in terms of internal disruption, etc., if these costs are overcome by the present abundance of internal funds or low current finance costs. Section I integrates the effect of financial conditions into the standard analysis to produce an estimable investment relationship. Section II describes the method of estimation. Section III presents results and conclusions.